Integrated marketing communication : a spiritual and an ethical Islamic perspective - Siti Aishah, Chu Abdullah; Mohd Nizam, Sahad (Inderscience Enterprises Ltd., 2016)
The purpose of this study is to ascertain the importance of spiritual elements and ethics to marketing strategy. The study uses critical review of the literature for insights on the integrated marketing communication (IMC) as an example of marketing strategy and Islam as a representative of spiritual elements and ethics. The study discovers that IMC could be highly potential in creating quality relationship with the consumers when the consumers’ religious values are emphasised. IMC is also in line with the Islamic marketing concept that focuses on the rhetoric of common good and prohibits organisations from abandoning the personal value of consumer. Notwithstanding the fact, the Muslims’ perspective of an integrated approach in marketing comes together with the humans’ duty as vicegerent of Allah SWT in order to sustain a good personality in this world and hereafter.